Observation of electron orbital signatures of single atoms within metal-phthalocyanines using atomic force microscopy - Pengcheng Chen; Dingxin Fan; Annabella Selloni; Emily A. Carter; Craig B. Arnold; Yunlong Zhang; Adam S. Gross; James R. Chelikowsky; Nan Yao (Nature Communications, 2023)
Resolving the orbital structure of single atoms is challenging and of great importance for understanding basic chemistry. Here, the authors demonstrate that the orbital occupation difference of single Fe/Co atoms within molecules can be distinguished with high resolution AFM imaging and spectroscopy.